New voyages to North-America : containing an account of the several nations of that vast continent, their customs, commerce, and way of navigation upon the lakes and rivers, the several attempts of the English and French to dispossess one another with the reasons of the miscarriage of the former, and the various adventures between the French and the Iroquese confederates of England from 1683 to 1694 : a geographical description of Canada and a natural history of the country with remarks upon their government, and the interest of the English and French in their commerce : also a dialogue between the author and a general of the savages, giving a full view of the religion and strange opinions of those people : with an account of the author's retreat to Portugal and Denmark and his remarks on those courts : to which is added, a dictionary of the Algonkine language, which is generally spoke in North America : illustrated with twenty three maps and cuts - Lahontan, baron de, 1666-1716.; Guedeville, Nicolas, approximately 1654-approximately 1721, attributed name.; Pre-1801 Imprint Collection (Library of Congress) DLC (London : Printed for J. and J. Bonwicke, R. Wilkin, S. Birt, T. Ward, E. Wicksteed, and J. Osborn, 1735)
Also a dialogue between the author and a general of the savages . with an account of the author's retreat to Portugal and Denmark, and his remarks on those courts. To which is added, a dictionary of the Algonkine language, which is generally spoke in North-America. Illustrated with twenty-three maps and cuts. This is one of two editions of two volumes published in 1735 with volume 2 printed by the same printers while volume 1 was printed by two different printers: Printed for J. Osborn, at the Golden Ball in Pater-Noster Row or Printed for J. Walthoe, R. Wilkin, J. and J. Bonwicke, J. Osborn, S. Birt, T. Ward and E. Wicksteed. Titles enclosed within double-rule border. Pagination: v.1: [24], 280 pages, [12] leaves of plates (some folded) : illustrations, maps (some folded) v. 2: [2], 3-304 pages, [10] leaves of plates (some folded) : illustrations. Some authorities consider Letter XVI, v. 1, which describes a voyage on Long River, which may have been Minnesota River as imaginary. The Indians described are for the most part also mythical. "A table explaining some terms made use of in both volumes": v. 1, p. 275-280. "A short dictionary of the most universal language of the savages": volume 2, pages 289-304. Imperfect: plates at p. 55, 160 and 184 wanting in v. 1. "A conference or dialogue between the author and Adario, a noted man among the savages": v. 2, p. 92-185. This has been attributed to Nicolas Gueudeville. Cf. Winsor, Nar. and crit. hist. of Amer., v. 4, p. 257-260. Vol. 2 has title and imprint: New voyages to North-America. Giving a full account of the customs, commerce, religion, and strange opinions of the savages of that country. With political remarks upon the courts of Portugal and Denmark, and the present state of commerce of those countries / written in French by the Baron Lahontan, lord lieutenant of the French colony at Placentia in Newfoundland, now in England. The second edition. Vol. II. London, Printed for J. Walthoe, R. Wilkin, J. and J. Bonwicke, J. Osborn, S. Birt, T. ...